025 Guest Lecture. Issue 10 (24th September 2010) - Vincent, A
Abstract : Abstract: It is well recognised that diseases of the peripheral nervous system can be caused by autoantibodies and respond well to immunotherapies associated with a fall in antibody levels. The best examples are, of course, myasthenia gravis and the Lambert Eaton myasthenic syndrome with antibodies to the acetylcholine receptor and voltage gated calcium channels respectively. In addition, Guillain Barre syndrome and Miller Fisher syndrome are associated with antibodies to gangliosides such as GM1 or GQ1b, although these conditions are not necessarily exclusively antibody-mediated. Over the last decade it has become clear that there are some CNS diseases strongly associated with specific antibodies to ion channels or receptors. Antibodies to GluR3 were first reported in Rasmussen's encephalitis, a rare but devastating form of childhood epilepsy for which the treatment is often hemispherectomy. In fact, there are now some doubts about how frequently these antibodies are found in Rasmussen's (Watson et al Neurology 2005) and they are measured routinely in very few centres. The general conception is that Rasmussen's is a T cell mediated inflammatory disorder and that the antibodies, if present, may not be the primary pathological entity. Antibodies to voltage-gated potassium channels, of the shaker-type that binds the snake toxin dendrotoxin, were first identified in patients with an acquired peripheral nerve hyperexcitability syndrome called Isaac's syndrome or neuromyotonia. This condition causes muscle twitching, fasciculations and cramps and is very uncomfortable but not life-threatening. It responds well to anti-epileptic drugs such as phenytoin, and immunotherapies are seldom required. Sometimes, however, neuromytonia is associated with autonomic dysfunction, sleep disorders, and cognitive impairment. This triad is usually referred to as Morvan's syndrome (Liguori et al Brain 2001). Although rare, it is highly interesting since the patients can present with such a range of symptoms, and some of their abnormalities reflect psychiatric disorders. A recent case reported by Spinazzi et al (Neurology 2008) illustrates this point. A 64 year old patient exhibited prominent compulsive behaviour with increased catecholamine and serotonin secretion as well as epileptic seizures and circadian rhythm suppression. Brain F-FDG-PET demonstrated markedly increased activity in the basal ganglia. Although the presence of multiple neurological signs suggested an organic disease, the history was complex and the diagnosis not clear for some time. Subsequently it was found that VGKC antibodies were clearly raised at 2000 pM, and indeed most of the symptoms and signs reversed following immunosuppressive treatment with a marked fall in VGKC antibodies. Basal ganglia hypermetabolism had not previously been reported with VGKC antibodies but is found in compulsive and psychotic disorders. Thus some of the features of Morvan's syndrome can mimic psychiatric disease. Much more common is VGKC-antibody associated limbic encephalitis (VGKC-LE) which is now a well recognised, most often non-paraneoplastic, form of LE. The VGKC antibodies are usually >400 pM often >3000 pM and fall dramatically following successful immunotherapies. These may include iv steroids, plasma exchange or intravenous immunoglobulins, and long-term high dose oral steroids that can be tapered to nil following clinical improvement. Most patients present with amnesia and seizures with personality change, but psychiatric presentations are not uncommon (Vincent et al 2004; Harrower et al 2006). High signal on MRI in the mesial temporal lobes, often restricted to the hippocampus, is found in the majority of patients. The cerebrospinal fluid is often unremarkable without oligoclonal bands or increased lymphocytes although protein may be slightly raised. Although the majority of patients do well following treatment, some relapse and anecdotal reports suggest that this may be due to lack of compliance or intolerance to steroids. On the other hand in some patients steroids clearly increases psychotic features. No clear guidelines to alternative therapies exist at this time. A new development is the finding that many of the antibodies to VGKCs are actually directed at other proteins that are complexed with the VGKCs in vivo. These new findings and their clinical associations will be described. Antibodies to glutamic acid decarboxylase are typically found at very high titre in stiff person syndrome. The antibodies themselves may not be pathogenic as GAD is an intracellular enzyme rather than a membrane protein. There may be other antibodies to neuronal cell surface membranes in these patients that are the pathogenic entity. Nevertheless, GAD antibodies are proving to be an important marker of immune-mediated neurological disease and found in an increasing number of patients with cerebellar ataxia, epilepsy and other neurological syndromes. Although not yet reported specifically in psychotic syndromes, it is well known that stiff person syndrome may be complicated by psychiatric features and it would not be surprising if some patients with psychosis turned out to have this antibody. Moreover, GAD antibodies can be associated with a form of epilepsy and limbic encephalitis, mainly in young females (Malter et al 2009). A newly described antibody to glycine receptors (GlyR) has been reported in one patient with an exaggerated startle response progressing to encephalomyelitis with rigidity and mycolonus (Hutchinson et Neurology 2008). Although only reported in a single case so far, this antibody has recently been found in other patients, mainly with a form of stiff person syndrome but some of whom exhibit psychiatric features (Leite, Vincent unpublished). One patient was diagnosed as psychogenic until the antibody was detected and has since been treated successfully with immunosuppression (unpublished results). Finally, the most exciting development is a form of autoimmune encephalitis that seems to present frequently with psychiatric features, although it then usually progresses to a full-blown encephalitis with marked movement disorders, mutism, catatonia, seizures and hypothalamic disturbance. NMDAR antibodies are associated with both paraneoplastic (ovarian tumours in young women) and non-paraneoplastic (both sexes but mainly younger patients so far) conditions. Both do well after treatments (removal of the tumour if relevant) although the long-term prognosis may not be so good in the non-paraneoplastic form (Dalmau et al Ann Neurol 2007; Lancet Neurology 2008). New data from our own cases will be presented. VGKC, GAD and NMDAR antibodies are now being searched in patients with various form of neuropsychiatric disorders and in a study of first episode psychosis (with Drs Brenda Lennox and Michael Zandi in Cambridge). This and further studies will determine how frequently these antibodies can be responsible for psychiatric disorders with obvious treatment and prognostic implications.